SMART ORGANIZERS AND THEIR ROLE IN MANAGING ATHLETIC TALENTS IN TEAMS OF PROFESSIONAL IRAQI BASKETBALL LEAGUE FROM PERSPECTIVE OF ADMINISTRATIVE BOARD MEMBERS AND TRAINING CREWS - Alsaqi, Ahmed Raad Ibrahim (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. Iraqi Professional Basketball League clubs face significant challenges in managing their athletic talents. These challenges include the lack of a clear vision for discovering and positively managing talents, providing their teams with distinguished athletic talents who can serve the clubs in various competitions. Many sports club administrations lack strategic planning to engage with these talents, developing them physically, skill-wise, and even psychologically, enabling them to build athletic personalities capable of handling athletic situations positively, free from stress and indiscipline. Furthermore, these clubs lack training programs and modern technologies that help hone these skills among many talented athletes, enabling them to identify strengths and weaknesses and address them quickly and effectively. Objectives. The purpose of this paper is to This research aims to identify the level of smart organizations and sports talent management within Iraqi professional basketball league clubs from the perspective of their administrative and technical staff. It also seeks to determine the extent to which smart organizations contribute to sports talent management within these clubs, again from the perspective of their administrative and technical staff. To achieve this primary objective, the researcher employed a descriptive methodology, deemed most suitable for the nature of this study. Method. The research sample comprised 57 members of the administrative and technical staff working in Iraqi sports clubs participating in the Iraqi professional basketball league for the 2024-2025 season. Results. The researcher utilized the arithmetic mean, standard deviation, percentage, and t-test. After statistically analyzing the data, the researcher concluded that Iraqi sports clubs participating in the Iraqi professional basketball league contribute to the management and development of sports talent, striving to achieve outstanding results and maintain a competitive edge. Conclusion. Iraqi sports clubs participating in the Iraqi Professional Basketball League are considered smart organizations that seek to develop, modernize, and address issues and events according to unconventional administrative procedures. Iraqi sports clubs participating in the Iraqi Professional Basketball League contribute to managing and nurturing sports talent to achieve outstanding results and maintain a competitive advantage.